Morphological features of doxorubicin-resistant Walker 256 carcinosarcoma and response of mast cells - Boroday, N.V.; Chekhun, V.F. (Experimental Oncology, 2018)
Background: The mechanisms of drug resistance of cancer have not been yet elucidated in details. Recently, the role of mast cells (MCs) in the development of drug resistance has been brought in the limelight. The aim of the study was to examine the morphological features of doxorubicin (DOX)-resistant Walker 256 carcinosarcoma and to assess the response of MCs and histamine content in these cells in relation to the development of resistance to DOX as well as in DOX-resistant tumors. Materials and Methods: The DOX resistance was induced by serial passages of Walker 256 carcinosarcoma in rats in the setting of DOX treatment in vivo. MCs in tumors were detected in the sections by staining with Toluidine Blue O. Histamine content in MCs stained with solution of Water Blue-Orcein was assessed by Astaldi semiquantitative method taking into account different staining intensity. Results: Formation of DOX resistance in the course of serial passages of Walker 256 carcinosarcoma was accompanied by the increase in the number of MCs in tumors and histamine content. Nevertheless, in tumors with phenotype of complete DOX resistance the number of histamine-containing MCs decreased to the same level as in tumors of the original strain that are DOX-sensitive. Conclusion: MCs are involved in formation of DOX resistance in Walker 256 carcinosarcoma.